BOPAK (Book of Plans Akhlakul Karimah) Berbasis Barcode untuk Meningkatkan Akhlakul Karimah Kelas IV SD - Feni Anggraeni; Alya Syifani; Nanda Nurfadhillah; Ani Nur Aeni (Lisyabab : Jurnal Studi Islam dan Sosial, 2022)
The development of cultural globalization that is currently happening does not reflect the noble character and norms in the country of Indonesia, and the Islamic religious law is widely imitated by children through the internet. Therefore, it is necessary to strengthen morals and strong implementation so as not to fade the moral values ​​of the nation's successors. The BOPAK (Book Of Plans Akhlakul Karimah) product is a semi-digital learning media development which contains material on Akhlakul Karimah, this material is contained in a book and in the form of an animated video that can be accessed in the form of a barcode. This book also does not only contain material, but there is a mission to complete each akhlaq karimah material that can be done by students which aims to strengthen akhlaq karimah attitude for students. This research and development aims to: (1) find out the results of product validation as an effort to improve the morals of fourth grade elementary school students, (2) develop conventional book-based learning into semi-digital-based interactive audio-visual media using barcodes. For data collection, this study used a D&D research approach. The product will be validated by several experts including teachers, and students through three aspects of assessment, namely aspects of media, learning, and material. From the results of research that has been carried out regarding the effectiveness of using BOPAK products by students and teachers, the majority get scores with very good criteria. The statement stated that this barcode-based book learning media was very helpful as a source of moral cultivation for elementary school students based on the conversion of assessment criteria.